PENGEMBANGAN MEDIA DIGITAL STORYTELLING PADA PEMBELAJARAN BAHASA INDONESIA SDN 158 PALEMBANG - Muhammad Sirajuddin; Liza Murniviyanty; David Budi Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning media is an important factor in the learning process. One of the problems of education in Indonesia is the limited use of learning media in the learning process. The purpose of this study was to determine the validity, practicality, and effectiveness of digital storytelling media in Indonesian language learning at SDN 158 Palembang. The research method used was the R&D (Research and Development) method with the ADDIE development model. The results of the study showed that the validity aspect obtained from the validator or experts obtained an average percentage of expert validation results of 92% so that it falls into the "very valid" criteria. The results of the user trial were 94%, the small group trial was 94.8%, and the big group trial was 92.72%. Based on the percentage of the trial results, it can be concluded that digital storytelling media obtained an average percentage of 93.84% so that it meets the "very practical" criteria. The post-test assessment data obtained a percentage of 92.59%. So it can be concluded that the digital storytelling media developed falls into the "very effective" criteria. So it can be concluded that the development of digital storytelling media in Indonesian language learning at SDN 158 Palembang is very feasible to use because it obtained the categories "very valid", "very practical", and "very effective"